KONSERVASI ANGGREK ALAM INDONESIA Vanda tricolor Lindl. varietas suavis MELALUI KULTUR EMBRIO SECARA IN-VITRO - Rindang Dwiyani; Azis Purwantoro; Ari Indrianto; Endang Semiarti (Environmental Research Center (PPLH) of Udayana University, 2012)
Vanda tricolor Lindl. var. suavis is an Indonesian wild orchid which is now extremely rare in nature due to its habitat destruction. Development of an appropriate method for propagation of this species through in vitro culture could be nessecary for conservation purposes. High phenolic content of plant tissue is a serious problem for V. tricolor research in the laboratory, which inhibits germination and growth of the embryo. To overcome this problem, seeds were sown in a medium with the addition of tomato extract as an antioxidant. The aim of this research is to find the most suitable concentration of tomato extract for germination and growth of the embryo of V. tricolor form Bali and Merapi in order to obtained healthy seedlings for conservation purposes. Orchid pods (7 months after polination) of V. tricolor Bali and Merapi were used as plant material. The treatment consisted of 5 concentrations of tomato extract which is 0, 50 100, 150, 200, 250 g L-1. Observation was done by counting the number of protocorms for each stage of growth at 4 weeks after seed sowing. The study concluded that V. tricolor Bali is more responsive to the tomato extract compared with Merapi. Concentration of 150 gL-1 tomato extract gave the highest percentage of protocorms for Bali form, whereas Merapi form did not give significant differences either with or without tomato extract added in the culture medium.